Hybrid thermoplastic composite reinforced natural fiber and inorganic filler - Cavdar, Ayfer Donmez; Torun, Sevda Boran; Pesman, Emrah; Angin, Naile; Ertas, Murat; Mengeloglu, Fatih (Walter De Gruyter Gmbh, 2023)
This chapter summarizes the recent studies on natural and synthetic short fiber-filled thermoplastic-based hybrid composites. This review will provide information on the manufacturing processes and the structure, and the properties of hybrid thermoplastic composites, in separate sections. It supplies data on physical, mechanical, morphological, rheological properties, and thermal and flammability characterizations of select hybrid composites. This chapter underlines the importance of hybrid thermoplastic composite in achieving predetermined material performances. Recent studies have proven that the hybridizations of natural fiber and inorganic filler might provide exceptional and promising features.
Keywords: Natural Fiber; Inorganic Filler; Hybrid Thermoplastic Composites; Polymer matrix